Metabolic Aspects of Palladium(II) Potential Anti-Cancer Drugs - Carneiro, Tatiana J.; Martins, Ana S.; Marques, M. Paula M.; Gil, Ana M. (Frontiers in Oncology, 2020)
This mini-review reports on the existing knowledge of the metabolic effects of Pd(II) complexes with potential anticancer activity, on cell lines and murine models. Most studies have addressed mononuclear Pd(II) complexes, although increasing interest has been noted in bidentate complexes, as polynuclear structures. In addition, the majority of records reported in vitro studies on cancer cell lines, some including the impact on health cells, as potentially informative in relation side effects. Generally, these studies address metabolic effects related to the mechanisms of induced cell death and antioxidant defence, often involving the measurement of gene and protein expression patterns, and evaluation of the levels of reactive oxygen species or specific metabolites, such as ATP and glutathione, in relation to mitochondrial respiration and antioxidant mechanisms. An important tendency is noted towards the use of more untargeted approaches, such as the use of omic sciences e.g. proteomics and metabolomics. In the discussion section of this mini-review, the developments carried out so far are summarised and suggestions of possible future developments are advanced, aiming at recognising that metabolites and metabolic pathways make up an important part of cell response and adaptation to therapeutic agents, their further study potentially contributing valuably for a more complete understanding of processes such as biotoxicity or development of drug resistance